Education beyond crisis : challenges and directions in a multicultural world - Andron, Daniela Roxana; Gruber, Gabriela (ISATT conference series, 2020)
"This book intends to find a common path for diverse approaches meant to reach a better vision on the future of education, to adapt it to the most spectacular and rapid changes in the modern world. Remarkable education specialists bring their research into this volume that collects the best ideas and solutions presented in the 19th Biennial Conference of the International Study Association on Teachers and Teaching (Sibiu, Romania, July 2019). The 17 chapters of this book promote a hopeful vision on the future of education as proclaimed in the title: Education beyond Crisis: Challenges and Directions in a Multicultural World. The volume focuses on three major ideas: defining directions for the future of teaching, challenges of the contemporary teaching context, and teaching in a multicultural world. The volume itself stands for the multicultural approach of education, as the contributors propose a unitary picture on education, in the contexts of national educative programs or inclusive education for the refugee children. Well-known researchers answer important questions on the effectiveness of educational reforms and education policies in different countries. They take into account the student voice or the teachers' opinions in teaching and designing the new curriculum. The volume includes researches based on case studies, interviews, surveys, qualitative analysis, and original researching instruments. Readers will find here not only the vision of a multicultural world, but also valuable ideas on education in Austria, Brazil, Canada, Portugal, Germany, Greece, India, Italy, the Netherlands, Pakistan, Serbia, Spain, Singapore, Romania, Turkey, and the United States. Contributors are: Christiana Deliewen Afrikaner, Laura Sara Agrati, Ana Flavia Souza Aquiar, Neelofar Ahmed, Douwe Beijaard, Terence Titus Chia, Cheryl J. Craig, Feyza Doyran, Estela Ene, Maria Assunção Flores, Maria Antonella Galanti, Paula Martín Gómez, Christos Govaris, Heng Jiang, Stavroula Kaldi, Ria George Kallumkal, Manpreet Kaur, Julia Köhler, Malathy Krishnasamy, Virginia Grazia Iris Magoga, Maria Ines Marcondes, Paulien C. Meijer, Juanjo Mena, Raluca Muresan, Ingeborg van der Neut, Ida E. Oosterheert, Darlene Ciuffetelli Parker, Loredana Perla, Cui Ping, Snežana Obradović-Ratković, Maria Luisa Garcia Rodriquez, Minodora Salcudean, Gonny Schellings, Antonis Smyrnaios, Sydney Sparks, Alexandra Stavrianoudaki, Vassiliki Tzika, Evgenia Vassilaki, Viviana Vinci, Kari-Lynn Winters, Vera E. Woloshyn, Tamara Zappaterra, and Gang Zhu"--